2002
DOI: 10.1300/j155v07n01_02
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sexual Orientation on Body Image and Attitudes About Eating and Weight

Abstract: SUMMARY We assessed the effect of sexual orientation on body image and attitudes toward eating and weight using data collected from lesbians and heterosexual women in three US cities. Data were analyzed using ordinary least squares regression controlling for a number of demographic characteristics. Findings indicate that while lesbian sexual orientation is predictive of positive body image and fewer negative attitudes toward eating and weight, the effects are modest. Body mass index (BMI), frequency of exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…For example, lesbians are less likely than heterosexual women to adhere to traditional female gender-role norms and more likely to drink alcohol (Hughes, 2005; Hughes and Wilsnack, 1997)—factors that may increase risk for smoking. Conversely, lesbians tend to be more highly educated, in part because of fewer family roles and responsibilities (Rothblum and Factor, 2001), and they appear to be less influenced by societal pressures to be thin (Herzog, Newman, Yeh, and Warshaw, 1992; Owen, Hughes, and Owens-Nicholson, 2003; Siever, 1994)—factors associated with lower risk of smoking among women. Although interesting and potentially important, until population-based studies that include large samples of lesbians are more feasible, the above hypotheses will remain untested and the question of whether lesbians are more likely than heterosexual women to smoke will remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lesbians are less likely than heterosexual women to adhere to traditional female gender-role norms and more likely to drink alcohol (Hughes, 2005; Hughes and Wilsnack, 1997)—factors that may increase risk for smoking. Conversely, lesbians tend to be more highly educated, in part because of fewer family roles and responsibilities (Rothblum and Factor, 2001), and they appear to be less influenced by societal pressures to be thin (Herzog, Newman, Yeh, and Warshaw, 1992; Owen, Hughes, and Owens-Nicholson, 2003; Siever, 1994)—factors associated with lower risk of smoking among women. Although interesting and potentially important, until population-based studies that include large samples of lesbians are more feasible, the above hypotheses will remain untested and the question of whether lesbians are more likely than heterosexual women to smoke will remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high level of agreement between our categorization of participants in the Chicago sample as lesbian, bisexual, or heterosexual and their self-identity suggests that misclassification bias using this method is likely modest (Hughes, Haas, and Avery, 1997). We use the terms lesbian, bisexual, and heterosexual to be consistent with terms and definitions used in previous reports of the MWHS findings (e.g., Hughes, Haas, Razzano, Cassidy, and Matthews, 2000; Matthews, Brandenburg, and Hughes, 2004; Matthews et al, 2002; Matthews and Hughes, 2001; Matthews, Hughes, Osterman, and Kodl, 2005; Owen, Hughes, and Owens-Nicholson, 2003), and for ease of communication.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies report no difference in eating disorder prevalence between heterosexual women and sexual minority women (Feldman & Meyer, 2007;Yean et al, 2013), whereas others report that lesbians are less likely to have symptoms of disordered eating (Owens, Hughes, Owens-Nicholson, 2003;Siever, 1994). However, a study of youth in Norway showed that same-sex experiences are related to more symptoms of bulimia (Wichstrøm, 2006) and recent data from U.S. youth show LGB identification was associated with higher odds of purging and diet pill use (Austin, Nelson, Birkett, Calzo, & Everett, 2013;Rosario et al, 2014).…”
Section: Eating Disordersmentioning
confidence: 99%
“…For example, Share and Mintz (2002) found that lesbian women had significantly higher levels of body esteem than heterosexual women. Similarly, Owens et al (2002) reported that lesbian women had more positive body image and fewer negative attitudes about weight and eating compared to heterosexual women. Conversely, Beren et al (1996) found that lesbian and heterosexual women's body dissatisfaction did not differ significantly.…”
Section: Introductionmentioning
confidence: 97%
“…Research comparing body images of lesbian and heterosexual women are inconsistent; some researchers report significant differences in body image (Owens, Hughes, & Owens-Nicholson, 2002;Share & Mintz, 2002) whereas others report null findings (Beren, Hayden, Wilfley, & Grilo, 1996). For example, Share and Mintz (2002) found that lesbian women had significantly higher levels of body esteem than heterosexual women.…”
Section: Introductionmentioning
confidence: 99%